Do ṣukūk and Islamic indexes~act~as safe refuge to conventional stock markets? Evidence from Markov-switching CAPM approach - Slah Bahloul; Fatma Mathlouthi (Islamic Economic Studies (IES), 2022)
Purpose The objective of this paper is twofold. First, to study the safe-haven characteristic of the Islamic stock indexes and ṣukūk during the crises time. Second, to evaluate this property in the last pandemic. This study employs the daily dataset from June 15, 2015, to June 15, 2020, for the most affected countries by the earlier disease. Design/methodology/approach This study uses the Markov-switching Capital Asset Pricing Model (CAPM) approach and the basic CAPM for the main analysis and the safe haven index (SHI) recently developed by Baur and Dimpfl (2021) for the robustness test. Findings Based on Baur and Lucey's (2010) definition, empirical findings indicate that Islamic stock indexes cannot be a refuge throughout the crisis regime for all selected conventional markets. However, ṣukūk are a strong refuge in Brazilian, Russian and Malaysian markets. For the remainder countries, except Italy, the USA and Spain, the ṣukūk index offers weak protection against serious conventional market downturns. Similar conclusions are obtained during the COVID-19 global crisis period. Finally, results are confirmed by using the SHI. Originality/value To the best of the authors' knowledge, this paper is the first study that evaluates the safe haven effectiveness of the Islamic index and ṣukūk using the SHI in the most impacted countries by the COVID-19 outbreak.
Keywords: G01; G11; G15; 330; COVID-19; Islamic indexes; Markov-switching CAPM; Safe haven index; Safe havens; ṣukūk